English Language Proficiency of Tour Guides at a Historical Attraction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study the English language proficiency of tour guides at a historical attraction to suggest a guideline for developing their English language skills. The sampling group used includes 400 foreign tourists who have been to a historical attraction with Thai tour guides’ accompanying them using English language to communicate. The study’s result appears that an average level of the tourists’ opinions on English language proficiency of tour guides at the historical attraction is overall at a high level. When considered by aspects, presentation skill is at the highest level followed by communication skill with the use of appropriate language level and the tour guides ‘English language proficiency, respectively. However, considering the average level of the tourists’ opinions by gender, it is found that, overall, the averages of the two aspects: presentation skill and communication skill with the use of appropriate language level are significantly different at a statistic level of .05.